Literatur Review: Analisis Penerapan Experiential Marketing terhadap Kepuasan Pasien di Rumah Sakit - Arkaine Malvania; Diansanto Prayoga (Universitas Airlangga, 2023)
Background: Hospitals as health care provider organizations require specialized strategies in dealing with the challenges of increasingly competitive market competition. Marketing strategies are applied in order to achieve competitive advantage over their competitors. Objectives: This journal has the aim to find out the application of experiential marketing as a form of marketing technique that management can apply in improving patient satisfaction in hospitals. Methods: The procedure for this research uses a literature review approach using the PRISMA flowchart. Discussion: The study showed varying results related to implementation of experiential marketing dimensions in hospitals. There are five dimensions implemented by hospitals namely sense, feel, think, act, and relate. Patient satisfaction in the application of experiential marketing can have impact on long term of the patient loyalty and the level of repeat buying over healthcare products and services in hospitals. Conclusions: There is a positive influence between the application of five dimensions of experiential marketing with patient satisfaction in hospitals.